Egg-shell CuO/CeO2/Al2O3 catalysts for CO preferential oxidation - Mariño, Fernando Javier (2015)
Catalytic systems based on copper and cerium supported on γ-Al2O3 have shown to be extremely effective for CO preferential oxidation. In order to selectively oxidize carbon monoxide, it is desired that only CO can access to the active sites. Since the effective diffusion of H2 is higher than that of CO, an egg-shell type distribution is preferred. With the objective of modifying the radial distribution of the active phases in the catalyst particle, the effect of four variables of the impregnation process is analyzed: metal loading, support-solution contact time, impregnation temperature and drying time. Radial profiles of Cu and Ce show that the egg-shell type distribution is favored by low metal loading, short contact and drying times and by high impregnation temperature. The effect of such variables is stronger on copper profile than on cerium profile. Catalytic performance on COPROX was enhanced by egg-shell type distribution.